Differences in Cytokine Expression and STAT3 Activation between Healthy Controls and Patients of Unexplained Recurrent Spontaneous Abortion (URSA) during Early Pregnancy - Cai, JunYing; Li, MuJun; Huang, QianYi; Fu, XiaoQian; Wu, HuiMei (PloS one, 2016)
Unexplained recurrent spontaneous abortion (URSA) is a common complication of pregnancy. Although tolerance of the maternal immune system is considered to be essential for a normal pregnancy, the precise mechanism underlying the pathogenesis of URSA remains to be fully elucidated, albeit it is known to involve inflammation. Here, we examine the relationship between the expression of inflammatory cytokines and the activation of downstream signaling pathways in URSA patients. Decidual and peripheral blood samples were collected from 30 URSA patients and from 30 women with normal early pregnancies. Western blot analysis was used to measure the expression levels of signal transducers and activators of transcription 3(STAT3), phosphorylated STAT3(p-STAT3), and interleukin-17 receptor(IL-17R) in the decidual samples. Enzyme-linked immunosorbent assay was used to assess the levels of IL-17, IL-10, IL-6, and IL-23 in the peripheral blood and decidual samples. In the URSA patients, the IL-10 expression levels were lower than those in the control subjects (P<0.05), whereas IL-6, IL-17, and IL-23 were all expressed at higher levels(P<0.05). Furthermore, the expression levels of IL-17R and p-STAT3 were higher in the URSA patients, exhibiting a trend similar to that of IL-23. Our finding of increased IL-23 expression in the deciduae and peripheral blood of patients with URSA suggest that this maybe a contributing factor to the pathogenesis of this disease. Likewise, STAT3 activation through its phosphorylation, which was associated with the IL-23 increase, may also be involved in URSA pathogenesis. However, the precise pathogenic mechanism requires further study.